Meroterpenes from Marine Invertebrates: Structures, Occurrence, and Ecological Implications - Anna Aiello; Filomena D'Aniello; Concetta Imperatore; Marialuisa Menna (Marine Drugs, 2013)
Meroterpenes are widely distributed among marine organisms; they are particularly abundant within brown algae, but other important sources include microorganisms and invertebrates. In the present review the structures and bioactivities of meroterpenes from marine invertebrates, mainly sponges and tunicates, are summarized. More than 300 molecules, often complex and with unique skeletons originating from intra- and inter-molecular cyclizations, and/or rearrangements, are illustrated. The reported syntheses are mentioned. The issue of a potential microbial link to their biosynthesis is also shortly outlined.